2018
DOI: 10.1038/nrdp.2018.3
|View full text |Cite
|
Sign up to set email alerts
|

Vascular cognitive impairment

Abstract: The term vascular cognitive impairment (VCI) was introduced around the start of the new millennium and refers to the contribution of vascular pathology to any severity of cognitive impairment, ranging from subjective cognitive decline and mild cognitive impairment to dementia. Although vascular pathology is common in elderly individuals with cognitive decline, pure vascular dementia (that is, dementia caused solely by vascular pathology) is uncommon. Indeed, most patients with vascular dementia also have other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
358
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 459 publications
(370 citation statements)
references
References 207 publications
2
358
1
9
Order By: Relevance
“…Together, such neurovascular system dysfunction and altered cerebral blood flow are likely significant elements of the pathophysiological processes underlying vascular cognitive impairment [37], and may be a mechanism of cognitive dysfunction in patients with HF. Not surprisingly, treating vascular diseases is the primary method to prevent vascular cognitive impairment [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Together, such neurovascular system dysfunction and altered cerebral blood flow are likely significant elements of the pathophysiological processes underlying vascular cognitive impairment [37], and may be a mechanism of cognitive dysfunction in patients with HF. Not surprisingly, treating vascular diseases is the primary method to prevent vascular cognitive impairment [40]. …”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important in neurodegenerative disease populations (e.g. Alzheimer's disease and Parkinson's disease), where WMHs are very common findings (van der Flier et al, 2018) and have been shown to interact with neurodegeneration and contribute to cognitive deficits (Dadar et al, 2018c(Dadar et al, , 2019 and therefore their misclassification as GM may systematically bias the findings of such studies.…”
Section: Introductionmentioning
confidence: 99%
“…cases with dementia(van der Flier et al, 2018). Since they contribute to cognitive deficits and neurodegeneration, incorrectly segmenting them as GM can introduce a systematic error into studies in such populations.…”
mentioning
confidence: 99%
“…Several mechanisms link vascular disease to cognitive impairment. Historically, VaD has been associated with large vessel infarcts, however small vessel disease can also lead to cognitive decline and dementia [7]. A previous prospective study showed that at least seven different pathologies can predict VCI: large infarcts, lacunar infarcts, microinfarcts, myelin loss, arteriolosclerosis, cerebral amyloid angiopathy (CAA), and perivascular space dilation [8].…”
Section: Introductionmentioning
confidence: 99%